2009
DOI: 10.1021/jf901429d
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Key Odorants in Sauternes Wines through Aging

Abstract: Recent work has revealed the importance of polyfunctional thiols in young Sauternes wines, but very little is yet known about the fate of such compounds during aging in the bottle. In this study, two Sauternes wines were investigated by gas chromatography-olfactometry (GC-O) aroma extract dilution analysis (AEDA), gas chromatography-mass spectrometry (GC-MS), and gas chromatography-pulsed flame photometric detector (GC-PFPD) after XAD 2 and thiol-specific extractions. Most polyfunctional thiols (3-sulfanylprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 24 publications
3
63
2
Order By: Relevance
“…As fatty acid esters can also have high odour activity in aged dessert wines (Bailly et al 2009;Bowen and Reynolds 2012), the role of T. delbrueckii on the modulation of the sensory properties of Vino Santo, due to these aromatic esters, could be relevant. Certainly, ethyl cinnamate can be considered a good candidate for be odour-potent compounds in Vino Santo wine, whose content can vary significantly depending on the yeast metabolism, as this study demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…As fatty acid esters can also have high odour activity in aged dessert wines (Bailly et al 2009;Bowen and Reynolds 2012), the role of T. delbrueckii on the modulation of the sensory properties of Vino Santo, due to these aromatic esters, could be relevant. Certainly, ethyl cinnamate can be considered a good candidate for be odour-potent compounds in Vino Santo wine, whose content can vary significantly depending on the yeast metabolism, as this study demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study suggests that, although no single γ-lactone was found at concentrations above its odor threshold, the lactones in combination may contribute to the aroma of wine through synergistic effects (Cooke et al 2009). In contrast, a separate study correlated γ-nonalactone levels with prune-like aromas in aged red wine (Pons et al 2008), and numerous studies have correlated γ-and δ-lactones with the aroma of botrytized wines from Sauternes (Bailly et al 2009), Barsac, Loupiac (Sarrazin et al 2007a), Campania (sweet Fiano wines) (Genovese et al 2007), and Hungary (Tokaji Aszú) (Miklósy and Kerényi 2004). As less is known about the origins of fatty acid derivatives compared to other grape-derived volatile compounds, further research is warranted to better understand their formation and contribution to wine aroma.…”
Section: Fatty Acid Derivativesmentioning
confidence: 91%
“…64,68 These compounds, however, do not fully explain the citrus-like nuances. In the last decade, studies on Sauternes wines using gas chromatography-olfactometry methods revealed the importance of polyfunctional thiols in this respect, especially sulfanylaldehydes, sulfanylalcohols, and sulfanylesters.…”
Section: Aroma Composition Of Botrytized Winesmentioning
confidence: 97%